Cognitive strategies, motivation to learn, levels of well-being, and risk of dropout: an empirical longitudinal study to qualify ongoing university guidance services. - Jovanice Emily (ENDLESS: INTERNATIONAL JOURNAL OF FUTURE STUDIES, 2023)
The article refers to a longitudinal empirical study that aims to establish the relationship between certain factors that facilitate (or sometimes hinder) academic achievement, such as the motivation to study, the cognitive strategies used and the levels of well-being or discomfort expressed by indicators such as anxiety and depression. Therefore, it aimed to identify the role of these factors in the risk of student dropout. The study was carried out on a sample of 68 self-selected students enrolled in various careers at the "Roma Tre" University, who had fully completed the three consecutive surveys aimed at investigating their academic experience over a period of one year. The measurement tools used evaluated: a) “abandonment intentions” (Hardre & Reeve Scale, 2003); b) “levels of well-being / distress”, (Adult Self-Report ASR; Achenbach & Rescorla, 2003); c) cognitive / study strategies (self-regulated knowledge; Manganelli, Alivernini, Mallia & Biasi, 2015); d) motivational aspects (AMS Academic Motivation Scale, validated in Italy by Alivernini and Lucidi (2008). The results show how the risk of dropping out is related to high levels of depression or anguish, low competence in the cognitive strategies adopted and high levels of of "Amotivation" and "External Motivation" Based on the previous empirical evidence, we propose to implement concrete and continuous actions within university guidance services in order to simultaneously improve well-being through emotional support, redefine decisions in the trajectory of study according to personal motivation, and develop adequate cognitive strategies to design a functional study method.